Використання нейромереж для створення текстів, зображень і відео в рекламі - Ольховик, О. І.; Вовк, О. В. (ХНУРЕ, 2025)
Modern digital advertising actively utilizes artificial intelligence (AI) to automate content creation. Manually generating texts, images and videos is a labor-intensive process that requires significant resources. The use of neural networks allows for the automation of this process, significantly reducing content development time and enhancing its personalization. The application of these technologies enables the automation of advertising material testing, content adaptation to the target audience, and consistency in style. Research shows that neural networks are a promising tool for marketers, advertising agencies, and digital specialists.
Keywords: створення текстів; відео в рекламі